The interplay of histone modifications - writers that read - Zhang, Tianyi; Cooper, Sarah; Brockdorff, Neil (EMBO reports, 2015)
Histones are subject to a vast array of posttranslational modifications including acetylation, methylation, phosphorylation, and ubiquitylation. The writers of these modifications play important roles in normal development and their mutation or misregulation is linked with both genetic disorders and various cancers. Readers of these marks contain protein domains that allow their recruitment to chromatin. Interestingly, writers often contain domains which can read chromatin marks, allowing the reinforcement of modifications through a positive feedback loop or inhibition of their activity by other modifications. We discuss how such positive reinforcement can result in chromatin states that are robust and can be epigenetically maintained through cell division. We describe the implications of these regulatory systems in relation to modifications including H3K4me3, H3K79me3, and H3K36me3 that are associated with active genes and H3K27me3 and H3K9me3 that have been linked to transcriptional repression. We also review the crosstalk between active and repressive modifications, illustrated by the interplay between the Polycomb and Trithorax histone‐modifying proteins, and discuss how this may be important in defining gene expression states during development. Graphical Abstract Post‐translational histone modifications correlate with gene expression states. This review discusses how these modifications are formed, reinforced and maintained, and how their crosstalk might define gene expression states.